RISK MANAGEMENT IN CONTAINER TERMINAL IN PORT OF TANJUNG PRIOK - Sirait, David Pandopotan; Besiou, Maria (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2017)
Container Terminal Operations is one of the core business of PT Tanjung Priok Port, the purpose of this study is to identify operational risks container service activities in Tanjung Priok and formulate mitigation efforts in order to ensure the sustainability of its business. Enterprise Risk Management (ERM) has a relationship that is important in the practice of Business Continuity Management (BCM). Risk identification and treatment in general have been mapped in the ERM practices are organized in order to support the achievement of corporate goals. ERM identify, analyze, and manage enterprise risks in general, where it is a first step in making the concept of BCM.The method used is a qualitative and quantitative analysis through the process of Risk Control Self Assessment and Business Impact Analysis. The respondent were General Manager and all staff in PT Tanjung Priok Port. The result showed that there are two significant risks in container terminal is a risk that is not a reliable IT systems and labor strikes. Mitigation conducted on each risk is procuring generators and UPS to anticipate IT system down and the preparation of a Business Continuity Plan to anticipate a labor strike.